Miyoshi myopathy and limb girdle muscular dystrophy R2 are the same disease - Moore, Ursula; Gordish, Heather; Diaz-Manera, Jordi; James, Meredith K.; Mayhew, Anna G.; Guglieri, Michela; Fernandez-Torron, Roberto; Rufibach, Laura E.; Feng, Jia; Blamire, Andrew M.; Carlier, Pierre G.; Spuler, Simone; et al. (Neuromuscular disorders : NMD, 2021)
•Initial diagnosis does not predict subsequent pattern of muscle weakness in dysferlinopathy.•Pattern of weakness is an overlapping continuum that does not form two distinct subgroups.•MM is a more common diagnosis in Japan than in Europe or the USA, but patients are not weaker distally.•Patients should not be split into MM and LGMDR2 subgroups for clinical trials. This study aims to determine clinically relevant phenotypic differences between the two most common phenotypic classifications in dysferlinopathy, limb girdle muscular dystrophy R2 (LGMDR2) and Miyoshi myopathy (MMD1). LGMDR2 and MMD1 are reported to involve different muscles, with LGMDR2 showing predominant limb girdle weakness and MMD1 showing predominant distal lower limb weakness. We used heatmaps, regression analysis and principle component analysis of functional and Magnetic Resonance Imaging data to perform a cross-sectional review of the pattern of muscle involvement in 168 patients from the Jain Foundation's international Clinical Outcomes Study for Dysferlinopathy. We demonstrated that there is no clinically relevant difference in proximal vs distal involvement between diagnosis. There is a continuum of distal involvement at any given degree of proximal involvement and patients do not fall into discrete distally or proximally affected groups. There appeared to be geographical preference for a particular diagnosis, with MMD1 being more common in Japan and LGMDR2 in Europe and the USA. We conclude that the dysferlinopathies do not form two distinct phenotypic groups and therefore should not be split into separate cohorts of LGMDR2 and MM for the purposes of clinical management, enrolment in clinical trials or access to subsequent treatments.